2006
DOI: 10.1126/science.1127980
|View full text |Cite
|
Sign up to set email alerts
|

Human Lineage–Specific Amplification, Selection, and Neuronal Expression of DUF1220 Domains

Abstract: Extreme gene duplication is a major source of evolutionary novelty. A genome-wide survey of gene copy number variation among human and great ape lineages revealed that the most striking human lineage-specific amplification was due to an unknown gene, MGC8902, which is predicted to encode multiple copies of a protein domain of unknown function (DUF1220). Sequences encoding these domains are virtually all primate-specific, show signs of positive selection, and are increasingly amplified generally as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
207
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(214 citation statements)
references
References 16 publications
4
207
1
2
Order By: Relevance
“…Interestingly, NBPF/DUF1220 sequences show human lineage-specific copy number increases (Dumas et al, 2007), consistent with previous reports (Fortna et al, 2004;Vandepoele et al, 2005;Popesco et al, 2006). Different experiments indicated that the number of NBPF/DUF1220 repeats was very large in humans, reduced in African great apes, further reduced in orangutan and Old World monkeys, single-copy in non-primate mammals, and absent in non-mammalian species (Popesco et al, 2006). The dramatically elevated copy number in humans indicates the importance of the NBPF/DUF1220 repeat in human evolution.…”
Section: The Nbpf Gene Family and Human Evolutionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, NBPF/DUF1220 sequences show human lineage-specific copy number increases (Dumas et al, 2007), consistent with previous reports (Fortna et al, 2004;Vandepoele et al, 2005;Popesco et al, 2006). Different experiments indicated that the number of NBPF/DUF1220 repeats was very large in humans, reduced in African great apes, further reduced in orangutan and Old World monkeys, single-copy in non-primate mammals, and absent in non-mammalian species (Popesco et al, 2006). The dramatically elevated copy number in humans indicates the importance of the NBPF/DUF1220 repeat in human evolution.…”
Section: The Nbpf Gene Family and Human Evolutionsupporting
confidence: 80%
“…Notably, the most striking trend in human evolution is the rapid increase in brain size over the past 3-4 million years, and the associated increase in complexity and cognitive capacity (Mekel-Bobrov et al, 2007). Because NBPF/DUF1220 is present in remarkably more copies in the human genome than in other primates (Vandepoele et al, 2005;Popesco et al, 2006), it was hypothesised that the NBPF/DUF1220 copy number is correlated with brain size (Dumas & Sikela, 2009). Moreover, these data support the hypothesis that NBPF/DUF1220 domains are involved in the difference in brain size between autistic and schizophrenic populations and between macrocephalic and microcephalic populations.…”
Section: 3mentioning
confidence: 99%
“…Finally, we note that HOTS joins a relatively small group of primate-specific proteins, including the POTE (expressed in prostate, ovary, testis, and placenta) gene family (33) and MGC8902, a human lineage-specific protein thought to be involved in higher cortical function (34).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in centrosomal proteins cause microcephaly. 17,18 Recently, it has been demonstrated that centrosomal proteins are essential for microtubule organization and centrosome motility that have important roles in axonal formation. 19 ZNF238 is a POZ/zinc finger transcriptional repressor gene.…”
Section: Deletion Of 1q43-q44 Scs Nagamani Et Almentioning
confidence: 99%